If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4 = 15x + 6 Reorder the terms: 4 + 5x = 15x + 6 Reorder the terms: 4 + 5x = 6 + 15x Solving 4 + 5x = 6 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 4 + 5x + -15x = 6 + 15x + -15x Combine like terms: 5x + -15x = -10x 4 + -10x = 6 + 15x + -15x Combine like terms: 15x + -15x = 0 4 + -10x = 6 + 0 4 + -10x = 6 Add '-4' to each side of the equation. 4 + -4 + -10x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -10x = 6 + -4 -10x = 6 + -4 Combine like terms: 6 + -4 = 2 -10x = 2 Divide each side by '-10'. x = -0.2 Simplifying x = -0.2
| -1-2(2a+1)=-7-4a | | 8m+7m=5m+16 | | 2N=3N-12 | | 6-4d=26-9d | | 3[3-(t+3)]-t= | | 800-(5*100)= | | -8x+2[2x-(4-5x)]= | | (2s)-2=s+64 | | 0.2x-3.8=-9 | | 3x+9=2x-7 | | (x-7)+3(x-1)=8x+6 | | 81-t^2=0 | | 9y-187=11y-253 | | 44x^2-192x^3+64x^2=0 | | 5x-3(x-1)=4-x | | 7x+3=2x+50 | | 15g=64+12g | | 800-5P=100+2P | | 4t^2-28t+13=0 | | 9x^2+27x+6=0 | | 60=x-16 | | 5x+6=2(-6+4x) | | (-4)+(-6)-(-2)-(-5)= | | 16+4x(7+8)-3=0 | | 2n-21=3n/4 | | 3r-7=11 | | 3-4+(-4)+(-8)= | | -14+1-4x+8x=8x+3 | | 3n^2+20n-7=0 | | 2n-21=2n/3 | | 5z+-19=64 | | x^2-25X+68=0 |